Rroid2 regulates effector-to-memory CD8 + T cell differentiation during infection in vivo - Julia Erber; Carmen Stecher; Valerie Plajer; Nina Braun; William Mallard; Loyal A. Goff; Iros Barozzi; Thomas Mohr; John L. Rinn; Richard A. Flavell; Dietmar Herndler-Brandstetter (Proceedings of the National Academy of Sciences, 2025)
CD8 + T cell differentiation has been associated with changes in the expression of long noncoding RNAs (lncRNAs). Yet, which and how lncRNAs regulate CD8 + T cell responses following infection in vivo remains incompletely understood. We performed deep RNA-seq to map the lncRNA expression landscape of CD8 + T cell subsets during infection and generated lncRNA knockout mouse models to evaluate the in vivo relevance of six lncRNAs. We identified Rroid2 to regulate effector CD8 + T cell function and effector-to-memory differentiation. Rroid2 -deficient mice displayed increased CD44 dim Foxp3 + regulatory T cells while the development of other immune cells, such as natural killer cells, was not affected. In CD8 + T cells, Rroid2 deficiency resulted in a fine-tuned downregulation of transcription factors Id2 and T-bet and impaired KLRG1 + and KLRG1 − effector CD8 + T cell proliferation and cytotoxicity as well as effector-to-memory CD8 + T cell differentiation. The human orthologue of Rroid2 , LINC01814 , is also upstream of the transcriptional regulator ID2 and is highly expressed in human memory CD8 + T cells. Taken together, Rroid2 represents a key regulatory layer that controls CD8 + T cell differentiation.